2009
DOI: 10.1007/s00701-009-0429-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of ApoE genotype with clinical features and outcome in idiopathic normal pressure hydrocephalus (iNPH): a preliminary report

Abstract: Fifteen patients suspected of having iNPH were clinically evaluated and their ApoE genotype determined prior to a possible ventriculoperitoneal shunt insertion. All patients fulfilling our criteria for intervention and who had a shunt implanted with good results were homozygous for the ApoE3/3 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Furthermore, APOE genotypes did not predict shunt response in our 121 shunted iNPH patients. Instead, in a series of 15 iNPH patients evaluated by gait analysis before and after CSF drainage, the APOE ɛ3/ɛ3 genotype seemed to predict improved gait 30. It should be noted that the cited study bears significant weaknesses, including a very small number of patients and no detection of primary or comorbid AD patients by means of brain biopsy, potentially invalidating the shunt response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, APOE genotypes did not predict shunt response in our 121 shunted iNPH patients. Instead, in a series of 15 iNPH patients evaluated by gait analysis before and after CSF drainage, the APOE ɛ3/ɛ3 genotype seemed to predict improved gait 30. It should be noted that the cited study bears significant weaknesses, including a very small number of patients and no detection of primary or comorbid AD patients by means of brain biopsy, potentially invalidating the shunt response.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the APOE4 allele is the most important independent genetic risk factor for late onset AD25–27 (http://www.alzgene.org). APOE4 is also associated with other neurological disorders,16 28 including iNPH 29 30. To date, the possible association of APOE and NPH has been explored in only two small cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…The increased allele frequency of apolipoprotein E epsilon4 (ApoE4) was reported to be a possible genetic risk for iNPH in a small number of iNPH samples (n = 13) [17]. Later, in another study (n = 15), the ApoE3/3 genotype was shown to be more frequently observed in shunt-responsive iNPH patients as compared with other genotypes [18]. However, in a recent study using more samples of iNPH, ApoE genotypes have been shown to distribute similarly in shunt-responsive (n = 94) and non-responsive (n = 16) iNPH patients and healthy controls [19].…”
Section: Discussionmentioning
confidence: 99%
“…APOE4 allele is the most significant independent genetic risk factor for late-onset AD [88][89][90] APOE4 is also correlated with other neurological diseases [91,92]. Studies showed that homozygous ApoE3/3 genotype was slightly associated with gait improvement in patients with iNPH but there was no other evidence for the correlation of APOE4 genotype, iNPH disease, and response to shunt [93][94][95].…”
Section: Apoe4mentioning
confidence: 99%